1993
DOI: 10.1063/1.110323
|View full text |Cite
|
Sign up to set email alerts
|

Experimental studies of ionization processes in the breakdown phase of a transient hollow cathode discharge

Abstract: The ionization process in the prebreakdown phase of a transient hollow cathode discharge (THCD) is investigated. The discharge is operated in H2 and N2 at pressures between 30 and 750 mTorr with applied voltages up to 30 kV. A capacitive probe array is used to measure the spatial and temporal evolution of plasma formation in the interelectrode spacing. The results obtained are consistent with the formation of a moving virtual anode. The growth and evolution of the virtual anode are closely linked to the format… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1994
1994
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Afterward, the discharge transfers to the final conductive phase, in which the cold cathode surface facing the anode takes over the whole discharge current with a very high current produced at a low acceleration potential until the gap is shorted. [18][19][20] The upper part of Fig. 3 shows a typical record of the time-correlated PS discharge voltage and beam current.…”
Section: Resultsmentioning
confidence: 99%
“…Afterward, the discharge transfers to the final conductive phase, in which the cold cathode surface facing the anode takes over the whole discharge current with a very high current produced at a low acceleration potential until the gap is shorted. [18][19][20] The upper part of Fig. 3 shows a typical record of the time-correlated PS discharge voltage and beam current.…”
Section: Resultsmentioning
confidence: 99%
“…Simulation has shown that the enhanced electron injection rate leads to the formation of a plasma region in the A-K gap, first near to the anode and then extending to the cathode, creating effectively a moving virtual anode, Manuscript received August 15, 1994;revised March 19, 1995 which brings the applied voltage close to the cathode and enhances the leakage field within the HCR [l]. The existence of this virtual anode was measured experimentally [ 2 ] . The electron extraction into the A-K gap leaves behind in the HCR a region rich in ions.…”
Section: Introductionmentioning
confidence: 99%
“…As the ionization growth continues, a virtual anode is formed, which propagates and extends the anode potential towards the cathode. 9 At the end of this phase, the full anode potential is brought close to the cathode and the electric field inside the HCR region is now significantly enhanced and local ionization is increased. The injection of an intense electron beam from this hollow cathode plasma source into the A-K gap then forms the final breakdown channel.…”
Section: Discussionmentioning
confidence: 98%